The effect of the SARS‐CoV‐2 pandemic and civil unrest on massive transfusion protocol activations in Minneapolis 2020. Issue 8 (28th May 2021) - Braun, Alexander L.; Gorlin, Jed B.; Peters, Jessica; Murphy, Sherrie; Van Buren, Nancy L.
Abstract: Background: The year 2020 presented the transfusion community with unprecedented events and challenges, including the ongoing SARS‐CoV‐2 (COVID‐19) pandemic, and more recently by civil unrest, following the death of George Floyd in late May of 2020. As a level 1 trauma center located in Minneapolis, Minnesota, Hennepin Healthcare (HCMC) offers a unique perspective into the changes in massive transfusion protocol (MTP) activations and usage during this tumultuous period. This may provide insight for addressing similar future events. Study design and methods: MTP logs from March 2020 to August 2020 were compared to logs from March to August 2019. The data were de‐identified, and MTP activations and component usage were categorized by activation reason. These categories were compared across the 2‐year period to examine the impact of COVID‐19, including stay‐at‐home orders, and civil unrest. Results: For the examined 6 months of the year 2020, there were a total of 140 MTP activations, compared to 143 in 2019. There were more activations for violent trauma (VT) in 2020 than 2019 (44 vs. 32). This increase in activations for VT was offset by a decrease in non‐trauma activations (54 vs. 66). There was a significant increase in the number of components used in VT activations. Discussion: During 2020, the initial mild decrease in MTP activations was followed by a dramatic increase in the number of activations and component usage for VT in June and July of that year.